RANCANG BANGUN SISTEM INFORMASI PEMESANAN ROTI BERBASIS WEBSITE PADA TOKO ROBADO BAKERY MENGGUNAKAN METODE WATERFALL - Sutresna, I Made; Putra, Made Adi Paramartha; Purnama, I Nyoman (Politeknik Bisnis Indonesia, 2025)
The rapid development of information technology has become an essential element in various aspects of life, including the business sector. Robado Bakery, which has been operating since 2018 in Nusa Penida, faces challenges in managing orders, which are still manually processed through WhatsApp. This practice leads to unorganized record-keeping, overproduction, and the unavailability of required bread stock. To address these issues, this study aims to design and develop a web-based bread ordering information system. This research adopts the waterfall development method, encompassing stages such as requirements analysis, system design, implementation, testing, and maintenance. Data collection was conducted through observation, interviews, and literature studies. The results show that the waterfall method remains relevant for the design and development of structured and integrated web-based information systems, particularly in the context of order management. The implemented system successfully improves order tracking, displays real-time stock information, and supports pre-order functions, thereby optimizing store operations and reducing operational inefficiencies.